2015
DOI: 10.1542/peds.2014-3675
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Celiac Disease: A Prospective Birth Cohort

Abstract: To investigate clinical features of celiac disease (CD) and their association with risk factors for CD in a genetic risk birth cohort.METHODS: Children from 6 clinical centers in 4 countries positive for HLA-DR3-DQ2 or DR4-DQ8 were annually screened for tissue transglutaminase antibodies (tTGA) and assessed for symptoms by questionnaires. Associations of symptoms with anthropometrics, known risk factors for CD, tTGA levels, and mucosal lesions in those biopsied were examined.RESULTS: Of 6706 screened children,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
67
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 29 publications
8
67
1
2
Order By: Relevance
“…In contrast, an older paediatric study found no such association, but it involved only 27 children [45]. We also detected an association between high autoantibody values and increased ALT, which is in line with the known correlation between serology and histology in celiac disease [46]. However, there is also evidence to indicate that the antibodies might in fact participate in the pathogenesis [10,11,47].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, an older paediatric study found no such association, but it involved only 27 children [45]. We also detected an association between high autoantibody values and increased ALT, which is in line with the known correlation between serology and histology in celiac disease [46]. However, there is also evidence to indicate that the antibodies might in fact participate in the pathogenesis [10,11,47].…”
Section: Discussionsupporting
confidence: 85%
“…This was in line with studies carried out in patients detected by other types of atrisk group screenings, for example first-degree relatives of coeliac disease patients (13,19). It also demonstrates that these individuals were very often not asymptomatic, just unrecognised.…”
Section: Discussionsupporting
confidence: 88%
“…In line with this, other recent studies conducted among screened children and adults have shown up to 34-84% of such patients to suffer from symptoms unrecognized at the time of the celiac disease diagnosis. 11,15,31,32 These findings demonstrate that symptom-based case finding is too inefficient to detect a large part of even children with classical gastrointestinal presentation, let alone those who present with atypical or subtle symptoms. What is more, most of the above mentioned pediatric screening studies have been conducted in Finland and other Nordic countries, where the disease is fairly well-known among pediatricians and primary care physicians, 15,32 and in many other countries the situation might be even poorer.…”
Section: Discussionmentioning
confidence: 98%
“…11,15,31,32 These findings demonstrate that symptom-based case finding is too inefficient to detect a large part of even children with classical gastrointestinal presentation, let alone those who present with atypical or subtle symptoms. What is more, most of the above mentioned pediatric screening studies have been conducted in Finland and other Nordic countries, where the disease is fairly well-known among pediatricians and primary care physicians, 15,32 and in many other countries the situation might be even poorer. For example, in the USA only 17% of all celiac disease patients were aware of their disorder before population screening, 33 and such underdiagnosing has also been observed in New Zealand and Australia.…”
Section: Discussionmentioning
confidence: 98%